The NN-explore Exoplanet Stellar Speckle Imager: Instrument Description and Preliminary Results. (13th April 2018) - Scott, Nicholas J.; Howell, Steve B.; Horch, Elliott P.; Everett, Mark E.
Abstract: A new speckle and wide-field imaging instrument for the WIYN telescope called NN-EXPLORE Exoplanet Stellar Speckle Imager (NESSI) is described. NESSI offers simultaneous two-color diffraction-limited imaging and wide-field traditional imaging for validation and characterization of transit and precision RV exoplanet studies. Many exoplanet targets will come from the NASA K 2 and Transiting Exoplanet Survey Satellite ( TESS ) missions. NESSI is capable of resolving close binaries at sub-arcsecond separations down to the diffraction limit and >6 mag contrast difference in the visible band on targets as faint as 14th mag. Preliminary results from the instrument commissioning at WIYN and demonstrations of the instrument's capabilities are presented.